MANAGERIAL ECONOMICS - KEATING BARRY (DREMTECH PUB)
MANAGERIAL ECONOMICS: AN INTRODUCTION AND OVERVIEW,THE ECONOMIC ENVIRONMENT OF BUSISNESS,OPTIMIZATION :FINDING THE BEST SOLUTION FOR BUSINESS DECISIONS,UNDERSTANDING AND BUILDING BUSINESS AND ECONOMIC MODELS
Keywords: ECONOMICS(B-12); ECONOMICS MANAGERIAL